A Critical View of Originalism in Bruen and Dobbs - Blåfield, Aada (My University, 2025)
The subject of the Thesis is the method of constitutional interpretation called originalism and its application in two U.S. Supreme Court cases from 2022 – Bruen and Dobbs. The study is theoretical. Alongside these two cases, New York State Rifle & Pistol Assn., Inc. v. Bruen and Dobbs v. Jackson Women’s Health Organization, it refers to a variety of articles such as Abandoning Original Meaning by Michael L. Smith and Originalism after Dobbs, Bruen, and Kennedy: the role of history and tradition by Randy E. Barnett and Lawrence B. Solum. The study is U.S.A. centric and its purpose is to obtain a deeper understanding of their legal climate today. The current academic understanding of originalism is that one should interpret the Constitution according to Original Public Meaning: the guidelines to interpretation should be how the piece of legislation was understood when it was ratified. The majority opinions of these two cases don’t reflect this perception. In fact, the perspective leans so heavily towards history and tradition of legislation regarding these matters, that they are better described as traditionalist rulings. Judicial appointment politics are one of the key factors in overruling Roe v. Wade in Dobbs. Originalism has provided an academic term that has been used a lot in discussing this. The sincerity of academic originalism is not under investigation here but the paper does present the question if, in light of the research, some political entities are using it as coded language for pushing conservative values.

ON-työn aiheena on originalismi eli Yhdysvaltojen perustuslain tulkintatapa, jossa keskitytään sen alkuperäiseen merkitykseen, ja sen soveltaminen kahdessa Yhdysvaltain korkeimman oikeuden tapauksessa vuodelta 2022. Tapausten nimet ovat New York State Rifle & Pistol Assn., Inc. v. Bruen ja Dobbs v. Jackson Women’s Health Organization. Tutkielmassa on käytetty teoreettista tutkimusmenetelmää. Näiden kahden tapauksen, Bruenin ja Dobbsin, ohella tutkielmassa käytetään useita artikkeleita, kuten Michael L. Smithin Abandoning Original Meaning sekä Randy E. Barnettin ja Lawrence B. Solumin Originalism after Dobbs, Bruen, and Kennedy: the role of history and tradition. ON-työ keskittyy Yhdysvaltoihin, ja sen tarkoituksena on saada syvällisempi ymmärrys maan nykyisestä oikeudellisesta ilmapiiristä. Tämänhetkinen akateeminen käsitys originalismista on, että sen mukaan perustuslakia tulisi tulkita alkuperäisen julkisen merkityksen mukaisesti. Tulkinnan ohjenuorana tulisi siis olla se, mitä säädöksen on ymmärretty tarkoittavan sen ratifioinnin aikaan. Kuitenkaan Bruenin ja Dobbsin enemmistön ratkaisut eivät ole tämän käsityksen mukaisia. Itse asiassa niiden keskiössä on pitkälti lainsäädännön historia ja perinteet, eikä säätämisenaikainen tulkinta. Tästä syystä niitä voidaan ennemminkin nimittää traditionalistisiksi ratkaisuiksi. Poliittinen taktikointi tuomareiden nimitysten suhteen on yksi keskeisistä tekijöistä Dobbsissa tapahtuneesta Roe v. Wade -ennakkopäätöksen kumoamisesta. Originalismia akateemisena käsitteenä on käytetty laajalti näissä keskusteluissa. Tutkielmassa ei tarkastella akateemisen originalismin vilpittömyyttä, mutta tutkimustulosten valossa se kyseenalaistaa, käyttävätkö jotkut poliittiset tahot originalismia peitekielenä, kun tosiasiassa tarkoituksena on edistää konservatiivisia arvoja.
Keywords: Originalism, case law, U.S. Constitution, originalismi, oikeuskäytäntö, Yhdysvaltojen perustuslaki